Long-term administration of bezafibrate on primary biliary cirrhosis - FURUKAWA, Ryuji; YANO, Koji; MORITA, Shigeki; KATO, Hiroyuki (Kanzo, 2002)
Bezafibrate is a commonly used drug for hyperlipidemia. Recently, it's additional effect of reduction of biliary enzymes, including serum alkaline phosphatase (ALP) activity, has been reported. The short-term therapeutic effect of bezafibrate on primary biliary cirrhosis (PBC) is promising. In the present report, we evaluated 13 PBC cases treated with ursodeoxycholic acid (UDCA), bezafibrate, or both. Further, we have used bezafibrate for PBC patients for relatively long-term in some cases (median: 6.0 years). Our experience supports the idea that bezafibrate exert a sustained effect on PBC patients. Notably, bezafibrate was effective in two patients to whom UDCA was not effective. No serious side effects were noted. Bezafibrate may be useful in long-term therapy for PBC.